A case of a delayed granulomatous reaction on the face following microneedling: A case report. (June 2022) - Heck, Emma; Traboulsi, Danya
Background: Microneedling is a common non-invasive procedure used for a variety of dermatologic conditions. It is associated with a low rate of adverse events which are typically temporary. Hypersensitivity reactions, including granuloma formation, are a rare adverse event, with only 10 cases previously reported. Case Summary: We report a case of a 49-year-old female who presented with asymptomatic edematous erythematous annular plaques on her left cheek following a microneedling procedure in which a Vitamin C cosmeceutical was applied to the skin beforehand. Skin biopsy confirmed non-necrotizing granulomatous dermatitis with negative tissue cultures. Systemic workup for sarcoidosis was negative. Conclusion: Delayed facial granulomatous reaction is an uncommon adverse event following microneedling. Increased risk may be related to peri-procedure use of cosmeceuticals such as Vitamin C. Given the popularity of microneedling, and that it is an unregulated procedure, it is important for dermatologists to be aware of this possible sequela in order to counsel patients appropriately and understand management options.